Liver blood marker testing in UK primary care: a UK wide cohort study, 2004–2016. Issue 9 (26th September 2022) - Scutt, Polly; Ban, Lu; Card, Tim; Crooks, Colin John; Guha, Neil; West, Joe; Morling, Joanne R
Abstract : Objective: We aimed to determine (1) the temporal trends of liver enzyme testing in UK general practice and (2) how these vary among different subgroups at risk of chronic liver disease (CLD). Design: Retrospective cohort study. Setting: UK primary care database (Clinical Practice Research Datalink (CPRD)), 2004–2016. Participants: Patients aged 18 years or over, registered in the CPRD from 1 January 2004 to 31 December 2016. Outcome measures: The frequency of testing recorded within the study period in general practice was calculated for: alanine aminotransferase (ALT); aspartate aminotransferase (AST); gamma glutamyl transferase (GGT); alkaline phosphatase (ALP); bilirubin and platelets. Analyses were conducted in subgroups of patients at high risk of developing liver disease. Results: The study cohort included 2 912 066 individuals with median follow-up of 3.2 years. The proportion of patients with at least one measurement for ALT, ALP, bilirubin or platelet test gradually increased over the course of the study period and fell for AST and GGT. By 2016, the proportion of the population receiving one of more tests in that year was: platelet count 28.0%, ALP 26.2%, bilirubin 25.6%, ALT 23.7%, GGT 5.1% and AST 2.2%. Those patients with risk factors for CLD had higher proportions receiving liver marker assessments than those without risk factors. Conclusions: The striking finding that AST is now only measured in a fraction of the population has significant implications for routine guidance which frequently expects it. A more nuanced approach where non-invasive markers are targeted towards individuals with risk factors for CLD may be a solution.